War, Economy, and Power: From the Past to the Present - Imam Tri Wahyudi; Guntur Eko Saputro; Duarte, Editha Praditya; Muhammad Iqbal (Universitas Muhammadiyah Yogyakarta, 2026)
The study investigated the development of economic warfare as a means of political expression from the Napoleonic Continental Blockade to current sanctions and trade warfare. Using the Comparative Historical Analysis (CHA) methodology and a systematic literature review (SLR) of 20 journals indexed in Scopus and Web of Science (WoS) (2019–2025), the study disclosed the crucial strategic continuity and a major change from Territorial Blockades to what is being called ‘Weaponized Interdependence’ or control of global financial networks, technology supply chain, and digital interdependence. The study uncovered three analytical patterns: the increasing ‘normalization’ of sanctions as coercive diplomacy; the exercise of extraterritoriality through control of networks; and the adaptive resilience of target states through restructuring and diversification. The study analyzed the latest developments in 2026, particularly the United States Supreme Court ruling on the International Emergency Economic Powers Act (IEEPA) and 104% countervailing duties on Indonesian solar panels, to exhibit that dependence on executive discretion as a downstream coercive network has resulted in the situational creation of new institutional imbalances. For Indonesia, these aggressive tariff policies on major global economies, coupled with macroeconomic volatility, increasing trade warfare, and reconfigured global supply chains, have presented both potential and problematic situational trade opportunities. The study proposes situational trade opportunities for Indonesia, combining economic warfare with market diversification, regional financial architecture reform, and institutional preparedness.